147k views
1 vote
Pls answer me this :( ​

Pls answer me this :( ​-example-1

1 Answer

5 votes

Answer:

GIVEN :-


  • x = -(1)/(2)

  • y = (2)/(4) = (1)/(2)

  • z= -(2)/(8) = -(1)/(4)

TO VERIFY :-


  • x + (y + z) = (x + y) + z

SOLUTION :-

L.H.S. =


x+ (y + z)


=> -(1)/(2) + ((1)/(2) + (-1)/(4) )


=> -(1)/(2) + ((2 - 1)/(4) )


=> -(1)/(2) + (1)/(4)


=> (-2 + 1)/(4)


=> -(1)/(4)

R.H.S. =


(-(1)/(2) + (1)/(2) ) + (-1)/(4)


=> 0 - (1)/(4)


=> -(1)/(4)

∴ L.H.S. = R.H.S. (Verified)

User Kaloyan
by
5.0k points